Differentiation of Glioblastomas from Metastatic Brain Tumors by Tryptophan Uptake and Kinetic Analysis: A Positron Emission Tomographic Study with Magnetic Resonance Imaging Comparison - David O. Kamson; Sandeep Mittal; Amy Buth; Otto Muzik; William J. Kupsky; Natasha L. Robinette; Geoffrey R. Barger; Csaba Juhász (Molecular Imaging, 2013)
Differentiating high-grade gliomas from solitary brain metastases is often difficult by conventional magnetic resonance imaging (MRI); molecular imaging may facilitate such discrimination. We tested the accuracy of α[ 11 C]methyl-L-tryptophan (AMT)–positron emission tomography (PET) to differentiate newly diagnosed glioblastomas from brain metastases. AMT-PET was performed in 36 adults with suspected brain malignancy. Tumoral AMT accumulation was measured by standardized uptake values (SUVs). Tracer kinetic analysis was also performed to separate tumoral net tryptophan transport (by AMT volume of distribution [VD]) from unidirectional uptake rates using dynamic PET and blood input function. Differentiating the accuracy of these PET variables was evaluated and compared to conventional MRI. For glioblastoma/metastasis differentiation, tumoral AMT SUV showed the highest accuracy (74%) and the tumor/cortex VD ratio had the highest positive predictive value (82%). The combined accuracy of MRI (size of contrast-enhancing lesion) and AMT-PET reached up to 93%. For ring-enhancing lesions, tumor/cortex SUV ratios were higher in glioblastomas than in metastatic tumors and could differentiate these two tumor types with > 90% accuracy. These results demonstrate that evaluation of tryptophan accumulation by PET can enhance pretreatment differentiation of glioblastomas and metastatic brain tumors. This approach may be particularly useful in patients with a newly diagnosed solitary ring-enhancing mass.